Learning to be advantaged: The development of home advantage in high-level youth soccer - Staufenbiel, K.; Riedl, D.; Strauss, B. (International Journal of Sport and Exercise Psychology, 2018)
Home teams in soccer are more successful than away teams. To date, the underlying causes of home advantage are insufficiently understood and there is limited research on the psychological processes (e.g. learning) of competitors. Two studies were conducted to investigate the experience and perspective of high-level youth players regarding home and away games. Youth players` experience of being more successful in home games could lead to a different approach to home and away games when reaching professional status. First, the extent of home advantage in the highest soccer leagues of the male age groups U9 (under nine years), U11, U13, U15, U17 and U19 was examined and additionally the first division senior soccer in Germany (seasons 2011/2012 and 2012/2013, N = 7.606 games). In all age groups except the U9 a significant relative home advantage was found (altogether M = 55.42, standard deviation (SD) = 2.43, d = 2.23) that increased with age (f2 = 0.11). In the second study, N = 199 male players of the same youth leagues filled in a questionnaire on home and away games. From the very beginning youth players prefer to play at home and progressively believe to win more games on the home field. Further investigations on athletes` learning concerning home and away games could lead to an understanding of the causes underlying home advantage.